Evaluation of hydrocarbon reserves using integrated petrophysical analysis and seismic interpretation: A case study of TIM field at southwestern offshore Niger Delta oil Province, Nigeria - Victor Cypren Nwaezeapu; Kingsley Chimaobi Ezenwaka; Tuoyo Adetutu Ede (Egyptian Journal of Petroleum)
This study presents the log analysis results of a log suite comprising gamma ray (GR), resistivity (LLD), neutron (PHIN), density (RHOB) logs and a 3D seismic interpretation of TIM field located in the southwestern offshore of Niger Delta, Nigeria. This study focuses essentially on reserves evaluation of hydrocarbon-bearing sands. Well data were used in the identification of reservoirs as well as hydrocarbon presence and determination of petrophysical parameters. Three horizons that corresponded to selected sands tops (sand D, sand E, and sand F) were mapped after well-to-seismic tie. The three horizons marked the tops of reservoir sands and provide the structures for hydrocarbon accumulation. Structural depth maps were created from the mapped horizons. The structural style is dominated by widely spaced simple rollover anticline bounded by growth faults, and this includes down-to-basin faults, antithetic faults and synthetic faults. The petrophysical values – the porosity, net-to-gross, water saturation, hydrocarbon saturation that were calculated yielded an average porosity value of 0.23, water saturation value of 0.32 and an average net-to-gross value of 0.62. Hydrocarbon in-place was evaluated. The total hydrocarbon proven reserves for the mapped horizons (sand D, sand E, and sand F) were evaluated to be 39.04MMBO of oil, and 166.13BCF of gas for sand E. Keywords: Niger Delta, Petrophysics, Reserve estimation, Hydrocarbon saturation